2021
DOI: 10.3390/nu13020637
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Dependent Effects of 7,8-Dihydroxyflavone on Metabolic Health Are Associated with Alterations in the Host Gut Microbiome

Abstract: 7,8-Dihydroxyflavone (DHF) is a naturally occurring flavonoid that has been reported to protect against a variety of pathologies. Chronic administration of DHF prevents high-fat diet (HFD)-induced obesity in female, but not male, mice. However, the mechanisms underlying this sexual dimorphism have not been elucidated. We have discovered that oral DHF supplementation significantly attenuates fat mass, hepatic lipid accumulation, and adipose tissue inflammation in female mice. In contrast, male mice were not pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 73 publications
1
13
0
Order By: Relevance
“…We and others have previously reported that oral DHF administration protects female but not male mice from HFDinduced obesity (38,39). We also reported that paradoxically, DHF supplementation exacerbates some of the metabolic pathologies associated with HFD-feeding in male mice, including increasing hepatic lipid accumulation and adipose tissue inflammation (38). In our previous study, we discovered a novel role for DHF in modulating the gut microbiome of female, but not male, mice at an early time point, prior to any divergence in body weights between DHF-treated and control groups.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…We and others have previously reported that oral DHF administration protects female but not male mice from HFDinduced obesity (38,39). We also reported that paradoxically, DHF supplementation exacerbates some of the metabolic pathologies associated with HFD-feeding in male mice, including increasing hepatic lipid accumulation and adipose tissue inflammation (38). In our previous study, we discovered a novel role for DHF in modulating the gut microbiome of female, but not male, mice at an early time point, prior to any divergence in body weights between DHF-treated and control groups.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, members of Rikenella are also associated with obesity and gut epithelial injury (96,102). More importantly, these changes in the gut microbiome were highly predictive of subsequent protection from HFD-induced weight gain in female mice, while no such association was observed in male DHF-supplemented animals (38). Given these previous associations between the gut microbiome and the metabolic effects of oral DHF supplementation, the current study was designed to determine whether the gut microbiome is causally linked to the effects of DHF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heart (LV) lipid extracts were also prepared by Folch extraction 45 to be analyzed by TLC GC-MS as described previously. 46,47 Briefly, tissue extracts were dissolved in chloroform, 2% Triton X100 solution and subsequently evaporated under nitrogen and dissolved in water. Lipids were then separated by thin-layer chromatography (TLC) on silica gel-60 plates (Millipore Sigma, St. Louis, MO, USA) in heptane-isopropyl ether-glacial acetic acid (60:40:3, v/v/v) with authentic standards.…”
Section: Measurements Of Lipid Content In the Left Ventricle By Tlc G...mentioning
confidence: 99%